Validity Test of UCLA Loneliness Scale Version 3 Using the Rasch Model - Rahimmatussalisa, Rahimmatussalisa; Rinaldi, Martaria Rizky (Faculty of Psychology, Universitas Gadjah Mada, 2025)
The UCLA Loneliness Scale Version 3 is one of the main measurement tools in investigating loneliness. This study aimed to test the validity of the UCLA Loneliness Scale Version 3 with the Rasch Model. The validity test was conducted to improve the understanding of the psychometric properties of the scale in the Indonesian population. Participants were 250 adults aged 20-34 (176 men, 74 women). The results showed that the UCLA Loneliness Scale Version 3 is a multidimensional measurement instrument. One item did not meet the criteria of model fit. Considerations for future research are discussed in the article.